Belajar dan Pembelajaran: Urgensi Memahami Perbedaan Konseptual dalam Dunia Pendidikan - Amelia Putri Indahwati; M. Mamduh Winangun; Sri Usodoningtyas (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Misunderstandings in the application of the terms "learning" and "teaching" in Indonesian education still often occur. In fact, there are important differences between the two concepts that can have a direct impact on educational practice. This article examines the differences between these two concepts and their impact on formal educational practice. The approach used is a case study based on secondary data, such as curriculum documents, national education regulations, and previous related research. This analysis refers to Vygotsky's constructivist learning theory and Gagne's learning theory. The results of this analysis show that misunderstanding of this concept gives rise to less than optimal learning designs, wrong teaching tactics, and wrong tendencies in assessing student learning achievement. To overcome this, this article recommends re-emphasizing the operational definitions of these two terms in national climate policies.